Hak Kepemilikan Tanah Bagi Warga Negara Indonesia Yang Menikah Dengan Orang Asing - Nadia Ardine; Mey Lia Sari; Aisyah Resta Melati; Arifa Kurnia Suci; Asti Giri Anjani (International Forum of Researchers and Lecturers, 2023)
Land ownership rights are one of the fundamental human rights. However, land ownership rights for Indonesian citizens who marry foreigners are specifically regulated in Indonesian laws and regulations. These provisions aim to maintain state sovereignty and prevent land control by foreign parties. Based on Indonesian laws and regulations, Indonesian citizens who marry foreigners can only have rights to certain land, namely use rights, rental rights for buildings, ownership rights to apartment units, and ownership rights to residential or residential houses. Ownership rights to land can only be owned by Indonesian citizens. This research aims to examine the regulation of land ownership rights for Indonesian citizens who marry foreigners in Indonesian legislation. The law regarding mixed marriages is regulated in Article 57 of Law Number 1 of 1974 concerning Marriage. In essence, mixed marriages allow Indonesian citizens to choose the citizenship they will follow, whether the citizenship of the husband or wife, in line with the provisions of Article 26 of Law Number 12 of 2006 concerning Citizenship of the Republic of Indonesia. Indonesian citizens who undergo mixed marriages have the possibility to create a marriage agreement that allows the separation of property between spouses during the marriage period, while maintaining their citizenship status..